2012
DOI: 10.1111/famp.12009
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Aspects of Being the Parent of an LGBTQ Child

Abstract: Parenting an LGBTQ (lesbian, gay, bisexual, transgender, or queer) identified child presents unique opportunities for growth and development. This study focused on self-reported perceptions of the positive aspects of being the parent of an LGBTQ child. Participants (N = 142) were mothers (83.8%) and fathers (16.2%) of LGBTQ identified individuals who responded to an open-ended online survey. Thematic analysis revealed five primary themes: Personal Growth (open mindedness, new perspectives, awareness of discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 25 publications
7
70
0
5
Order By: Relevance
“…Consistent with previous research (Gonzalez et al, 2013;Phillips & Ancis, 2008;Saltzburg, 2009), an important aspect of the parents' personal growth and development and coming to a level of acceptance was the significance of social support and positive (re)connection within the familial unit as well as the community. At the time of the interviews, it was the mothers who appeared to have come out in the community, and took an activist role within their workplace and leisure contexts.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with previous research (Gonzalez et al, 2013;Phillips & Ancis, 2008;Saltzburg, 2009), an important aspect of the parents' personal growth and development and coming to a level of acceptance was the significance of social support and positive (re)connection within the familial unit as well as the community. At the time of the interviews, it was the mothers who appeared to have come out in the community, and took an activist role within their workplace and leisure contexts.…”
Section: Discussionsupporting
confidence: 85%
“…Parents report the need to conceal their child's LGB identity from others, enhanced conflict between siblings and parents, as well as a plethora of negative emotions wherein parents may experience emotions such as loss, fear, hurt, denial, self-blame, shame, guilt, or even despair (Goodrich, 2009). At the same time, parenting a child with a LGB identity may also present unique opportunities for parental growth, development and positive transformation (Gonzalez, Rostosky, Odom, & Riggle, 2013). For example, Gonzalez et al reported that some parents may eventually experience personal growth (e.g., open mindedness), positive emotions (e.g., pride), activism, social connection, and a closer relationship with their child.…”
Section: Coming-out-to-family and Parental Adjustmentmentioning
confidence: 99%
“…Goodrich (2009) focused on parents who had successfully integrated their experience since their child disclosed to them, describing an emergent model characterized by emotional, cognitive, and behavioral responses that led to a successful integration of their identity. A recent qualitative survey study by Gonzalez, Rostosky, Odom & Riggle (2013) found that many parents experienced and associated positive emotions, improved closeness, and personal growth with parenting an LGBTQ child.…”
Section: The Parent Perspectivementioning
confidence: 99%
“…The perception of how welcoming or hostile the social world outside the family can be for their children, and the possibility of imagining a happy life for them, emerge as important contextual conditions. In line with recent studies focusing upon the positive aspects of parents' experiences after disclosure (Gonzalez, Rostosky, Odom, & Riggle, 2013), Grafsky discusses how these positive narratives depart from the grieving processes through which parents' reaction to the coming out of a sexual minority child has often been interpreted.…”
Section: An Overview Of the Issuementioning
confidence: 89%
“…A thorough discussion on the implications of this recruitment requires that these organizations become themselves objects of inquiry, about how they shape meanings, identities, and motives for action (Broad, Crawley, & Foley, 2004;Broad, 2011;Johnson & Best, 2012), and about how they may reproduce hierarchies of gender and sexuality, but also of race and class (Broad, Alden, Berkowitz, & Ryan, 2008). Qualitative studies, based on small samples, have been recently joined by online surveys (Horne et al,2010;Conley, 2011;Gonzalez et al, 2013), which might also contribute to exploring differences between more active parents (and other family members) and those developing their coping strategies without contact with these organizations. What shapes parents' narratives is, however, a complex question to address.…”
Section: Further Questions and Directionsmentioning
confidence: 99%